Experimental modal analysis and model validation of antenna structures - Potgieter, Brendon Ryan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.